Open society : reforming global capitalism - Soros, George; Soros, George (New York : Public Affairs, 2000)
Examines economic theory and the causes of instability in an increasingly global economy, and discusses the concept of open society as a means of preventing financial disintegration
Thinking and reality -- A critique of economics -- Reflexivity in financial markets -- Reflexivity in history -- Open society as an ideal -- The problem of social values -- The global capitalist system -- The financial crisis of 1997-1999 -- Who lost Russia? -- A new global financial architecture -- The global political architecture -- The Open Society Alliance
Rev. edition of: The crisis of global capitalism, 1998.
Includes bibliographical references and index.
Keywords: Financial crises; Financial crises -- Social aspects; Capitalism -- Social aspects; International finance -- Social aspects; Globalization -- Social aspects; Democracy; Human rights; Economic history -- 1990-; World politics -- 1989-